Design of Investment Detection In Fish Cultivation Uno Arduino Based - Hasibuan, Arnawan; Asran, Asran; Sembiring, Rizky Ramadhana; Isa, Muzamir; Yusoff, Mohd Irwan; Abdul Rahim, Siti Rafidah (LPPM Universitas Andalas, 2021)
Fish farming is a job that many Indonesian people do, especially in villages. The nature of fish that is able to adapt quickly to transfer from pond to pond makes many residents choose to breed fish over other livestock. Many types of fish can be cultivated well, but most people choose to cultivate goldfish. Goldfish have an economic value that is quite tempting for the community. There are some fish that have a higher economic value, but people are more extra in maintaining them, for example in terms of feed. Goldfish can be fed only when the sun is hot. If the sun does not come out, then the goldfish should not be fed because it can cause the fish to die. Besides that, goldfish only need water flowing into the pond for fish oxygen. The number of people who breed fish, there are also many irresponsible people. The reason is, when the fish begin to grow up, many fish begin to disappear, making people nervous and hot. Based on the above problems, it provides a very potential opportunity to create a tool that can overcome community unrest. Fish farming theft detection tool which is an innovative tool to overcome or find out the perpetrators of theft. Thus, hopefully the tools used can reduce the risk of stealing fish and reduce the losses of fish cultivators.